1999
DOI: 10.1002/cbm.330
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of antisocial behaviour in early adolescence and adolescence: psychometric properties and substantive findings

Abstract: Background/Aims This article describes the development of a new self-report instrument, the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 38 publications
4
71
1
2
Order By: Relevance
“…Olweus (1994) quoted correlations of 0.4 -0.6 between self-reports of bullying experiences and independent peer ratings. Bendixen and Olweus (1999) found significant positive correlations between the Olweus Bully/Victim Questionnaire 'victim' behaviour items and a separate peer rejection scale, as well as between 'bully' behaviour items and independent measures of antisocial behaviour.…”
Section: Methodsmentioning
confidence: 86%
“…Olweus (1994) quoted correlations of 0.4 -0.6 between self-reports of bullying experiences and independent peer ratings. Bendixen and Olweus (1999) found significant positive correlations between the Olweus Bully/Victim Questionnaire 'victim' behaviour items and a separate peer rejection scale, as well as between 'bully' behaviour items and independent measures of antisocial behaviour.…”
Section: Methodsmentioning
confidence: 86%
“…Potential items were selected by reviewing existing measures of delinquency (which included items relating to general violence and non-violent offending) and partner violence and, in order to include a broad range of both violent and non-violent criminal acts (e.g., Bendixen & Olweus, 1999;Borjesson, Aarons, & Dunn, 2003;Dahlberg, Toal & Behrens, 1998;Huizinga, Esbensen, & Weiher, 1991;Mak, 1993;Moffitt & Silva, 1988;Moffitt et al, 1997;Straus, 1979;Straus, Hamby, Boney-McCoy, & Sugarman, 1996). Initially, 119 items were selected from the literature review and a pilot study was conducted to investigate the prevalence of the behaviors in women as violent and criminal scales tend to be developed on men.…”
Section: Methods Item Selectionmentioning
confidence: 99%
“…Bendixen and Olweus 1999;Junger-Tas et al 2003;Smith and McVie 2003), and a Portuguese self-reported frequency scale measuring adolescents' deviant behavior (see Sanches et al 2012). Items had different severity levels and pertained to 11 categories: thefts, alcohol and drugs consumption, verbal and physical aggression, possession of weapons, vandalism, truancy, driving without a license, assault, use of public transport without paying, lies and defiance of authority, and selling drugs.…”
Section: Measures/instrument Item Generationmentioning
confidence: 99%
“…Although variety scales are considered a reliable and valid measure and have been used for long (e.g. Bendixen et al 2003;Bendixen and Olweus 1999;Caspi et al 1994;Junger-Tas and Marshall 1999;Weerman and Bijleveld 2007), they seem to be gaining an increasing relevance recently, given the growing number of publications using this kind of scale (e.g. Brown and Jennings 2014;Cohn et al 2012;Donner et al 2014;Flexon, and Meldrum 2013;Hirtenlehner et al 2014;Intravia et al 2012;Malouf et al 2014;Megens and Weerman 2012;Meldrum et al 2012;Peck 2013;Trinkner et al 2012;Yu et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation